2023
DOI: 10.1021/jacs.3c11610
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Iron-Based Catalyst for Light-Driven Selective Hydrogenation of Nitroarenes

Jun Ma,
Xin Mao,
Canyu Hu
et al.

Abstract: Light-driven hydrogenation of nitro compounds to functionalized amines is of great importance yet a challenge for practical applications, which calls for the development of high-performance, nonprecious photocatalysts and efficient catalytic systems. Herein, we report a high-efficiency Fe 3 O 4 @TiO 2 photocatalyst via a sol−gel and subsequent pyrolysis strategy, which exhibits desirable photothermal hydrogenation performance of nitro compounds to functionalized amines with the excellent selectivity of >90% ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The selective hydrogenation of nitro compounds containing additional reducible groups such as alkene, carbonyl, and/or halide to produce functionalized amines poses a significant and challenging task in both contemporary chemical and pharmaceutical industry. 160–163 In this context, Ma et al 164 fabricated TiO 2 based iron oxide (Fe 3 O 4 @TiO 2 ) heterogeneous photocatalyst for the selective hydrogenation of nitroarenes into amine derivatives. The Fe 3 O 4 @TiO 2 photocatalyst was synthesized by the sol–gel approach followed by the pyrolysis process (Fig.…”
Section: Catalytic Applications Of Nanosized Iron Oxidesmentioning
confidence: 99%
“…The selective hydrogenation of nitro compounds containing additional reducible groups such as alkene, carbonyl, and/or halide to produce functionalized amines poses a significant and challenging task in both contemporary chemical and pharmaceutical industry. 160–163 In this context, Ma et al 164 fabricated TiO 2 based iron oxide (Fe 3 O 4 @TiO 2 ) heterogeneous photocatalyst for the selective hydrogenation of nitroarenes into amine derivatives. The Fe 3 O 4 @TiO 2 photocatalyst was synthesized by the sol–gel approach followed by the pyrolysis process (Fig.…”
Section: Catalytic Applications Of Nanosized Iron Oxidesmentioning
confidence: 99%
“…A recent report from the Zhao and Xiong groups detailed the use of a low-cost and high-performing Fe 3 O 4 –TiO 2 catalyst, which was able to successfully hydrogenate a diverse array of nitroarenes to afford the corresponding amine (Figure b) . Iron and titanium-based photothermal agents offer a more inexpensive and accessible catalyst, while addressing challenging reactivity.…”
Section: Hydrogenation and Oxidationmentioning
confidence: 99%
“…On the other hand, the concept of photo-thermal catalysis has been proposed in recent years. Photo-thermal catalysis integrates thermal catalysis and photocatalysis into a photo-thermal synergistic catalysis and exhibits a better catalytic performance than that of thermal catalysis and photocatalysis alone. Gao’s group found that Pd 3 Au 0.5 /SiC showed a 6 times greater turnover frequency under visible-light irradiation (1715 h –1 ) than in dark for the nitrobenzene hydrogenation under 0.1 MPa H 2 and 25 °C; they ascribed the outstanding catalytic performance to the synergistic effect of Pd and Au nanoparticles on the semiconductor SiC .…”
Section: Introductionmentioning
confidence: 99%